2018
DOI: 10.1111/inm.12451
|View full text |Cite
|
Sign up to set email alerts
|

Fear and blame in mental health nurses’ accounts of restrictive practices: Implications for the elimination of seclusion and restraint

Abstract: Restrictive practices continue to be used in mental health care despite increasing recognition of their harms and an international effort to reduce and ultimately eliminate their use. The aim of this qualitative study was to explore mental health nurses' views of the potential elimination of these practices. Nine focus groups were conducted with 44 mental health nurses across Australia, and the data analysed using thematic analysis. Overall, the nurses expressed significant fear about the potential elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
117
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(147 citation statements)
references
References 39 publications
10
117
0
2
Order By: Relevance
“…Given this evidence, it may be that for some participants in this review, separating from the reality of what was happening was a dissociative coping strategy in response to being retraumatized. Mental health staff, patients and their families have expressed concerns that seclusion is a traumatic intervention that could trigger memories of historical trauma (Brophy et al, ; Muir‐Cochrane, O'Kane, & Oster, ). Strout's () review of qualitative literature found that physical restraint is also experienced as retraumatizing.…”
Section: Discussionmentioning
confidence: 99%
“…Given this evidence, it may be that for some participants in this review, separating from the reality of what was happening was a dissociative coping strategy in response to being retraumatized. Mental health staff, patients and their families have expressed concerns that seclusion is a traumatic intervention that could trigger memories of historical trauma (Brophy et al, ; Muir‐Cochrane, O'Kane, & Oster, ). Strout's () review of qualitative literature found that physical restraint is also experienced as retraumatizing.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does this impact student experiences of their practicums and recruitment into the mental health field, but also suggests the need for a fundamental shift in the way mental health care is conceptualised and enacted. Literature demonstrates that nurses in these settings are caught in tension between desiring to engage in therapeutic relationships with patients, but perceiving practices that contain and control patients as necessary for safety and treatment (Slemon, Jenkins, & Bungay, ; Larsen & Terkelsen, ; Muir‐Cochrane, O'Kane, & Oster, ). Change initiatives are needed that shift the practices of care towards prioritising the therapeutic relationship and empowering patients, while also acknowledging the need for safety for all individuals in the inpatient mental health setting.…”
Section: Discussionmentioning
confidence: 99%
“…The fear of blame from an adverse event can result in a strong focus on documentation ‘to cover oneself’ (Manuel & Crowe ; Clancy & Happell ) as well as a reliance on restrictive practices (Slemon, Jenkins & Bungary ). For instance, fear and blame have been found to undermine attempts to eliminate seclusion and restraint in mental health care (Muir‐Cochrane, O'Kane & Oster ). Nurses can feel trapped between the policy of seclusion reduction on the one hand, and on the other hand, the imperative to protect themselves and others through the use of seclusion as a risk management strategy.…”
Section: Why Are Meaningful ‘Consumer Involved’ Care Plans Not Alwaysmentioning
confidence: 99%